(3eLehY cdGe GdTGaYi aj CMcGe GdbQBfs - (3CHh HcQ CMeO Hf GdMSjf Hf Ydj GdNQGSGfj GdTGaYj, GdHjgbj,J (B458 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf aUd PcQg GdTGaYi QMeg Gddg ai GdJMQjV Ydi JYde GMcGe GdbQBf s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde (B:( (3Ef GdReGf bO GSJOGQ cgjFJg jhe Ndb Gddg GdSehGJ hGdGQV GdSfI EKfG YTQ TgQkG efgG GQHYI MQe KdGKI eJhGdjGJ Ph GdbYOg hPh GdMLI hGdeMQe hQLH TgQ eVQ GdPi Hjf LeGOi hTYHGf (B) (3bGd GdTGaYi adG TgQ jfSC hSeGg QShd Gs
(3HgG fXGe GdJYbjHIs
(3cJHJ Yf fSNI eLehYI Ydi GdGeGe GdLhGQi GdHjgbi HQhGjJg Yf GdeUfa SeGYkG Gh HGdELGRI GdJi dGTc ajgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B116 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B206s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdJaSjQ hYdhe GdbQBfs